Determinants of risk of invasive cervical cancer in young women. - Parazzini, F. (Nature Publishing Group, 1998)
We analysed determinants of risk of cervical cancer in women aged less than 45 years using data from a case-control study conducted in Italy. Cases were 261 women aged < 45 years with histologically confirmed invasive cervical cancer. Controls were 257 women aged < 45 years, with acute, non-neoplastic conditions, judged to be unrelated to any of the known or suspected risk factors for cervical cancer. In comparison with women reporting one or no sexual partner, the multivariate odds ratio (OR) of cervical cancer was 2.4 (95% confidence interval, CI, 1.3-4.6), for women reporting two or more sexual partners, and, in comparison with women reporting their first intercourse at 17 years of age or before, the multivariate OR was 0.5 (95% CI 0.3-0.9) in women aged > or =23 years at first intercourse. The risk of cervical cancer was higher in parous women and increased with number of births (OR = 8.1 for three or more births). Among parous women the risk tended to increase with later age at last birth; in comparison with parous women reporting their last birth before age 25, the OR was 1.9 in those reporting their last birth at > or =35 years. No clear association emerged between oral contraceptive use, smoking, education, social class and risk of cervical cancer.